Tsunami Vulnerability in West Padang, North Padang and Koto Tangan Sub-Districts - Haryani, Haryani; Dianda, Alya Maghfira; Yeni Fitri, Yeni Fitri; Seftiyani, Friska (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
ABSTRACT: Padang City is one of the cities on the coast of West Sumatra, where coastal areas have the potential for tsunami disasters which can cause large losses. Therefore, it is necessary to know the level of vulnerability to tsunami disasters in order to mitigate disasters. According to BPBD Padang City in 2010, Koto Tangah Subdistrict, North Padang Subdistrict and West Padang Subdistrict are subdistricts with 28 villages that are included in the red zone, therefore it is necessary to study the level of tsunami vulnerability in the red zone of Koto Tangah Subdistrict, North Padang Subdistrict and West Padang Subdistrict. The secondary method is a data collection method in the form of population and GRDP obtained from BPS Padang City in Figures, building data obtained from the 2022 consultant digitization results, and land use data from the 2010-2030 RTRW of Padang City. As well as the analysis method, namely descriptive and quantitative analysis with the standards of Perka BNPB No. 02 of 2012 concerning General Guidelines for Disaster Risk Assessment. Based on the results of the analysis of the three sub-districts, there are 2 classifications, namely high and medium, for West Padang Sub-district all urban villages have a high level of vulnerability while the other 2 sub-districts have a high and medium level of vulnerability. Keywords: Vulnerability, Tsunami, Disaster, Padang